CRISPR-Cas12a System With Synergistic Phage Recombination Proteins for Multiplex Precision Editing in Human Cells - Wang, Chengkun; Xia, Qiong; Zhang, Qianhe; Qu, Yuanhao; Su, Stephen; Cheng, Jason K. W.; Hughes, Nicholas W.; Cong, Le (Frontiers in Cell and Developmental Biology, 2022)
The development of CRISPR-based gene-editing technologies has brought an unprecedented revolution in the field of genome engineering. Cas12a, a member of the Class 2 Type V CRISPR-associated endonuclease family distinct from Cas9, has been repurposed and developed into versatile gene-editing tools with distinct PAM recognition sites and multiplexed gene targeting capability. However, with current CRISPR/Cas12a technologies, it remains a challenge to perform efficient and precise genome editing of long sequences in mammalian cells. To address this limitation, we utilized phage recombination enzymes and developed an efficient CRISPR/Cas12a tool for multiplexed precision editing in mammalian cells. Through serial protein engineering, we were able to recruit phage recombination proteins to Cas12a to enhance its homology-directed repair efficiencies. Our phage-recombination-assisted Cas12a system achieved up to 3-fold improvements for kilobase-scale knock-ins in human cells without compromising the specificity of the enzyme. The performance of this system compares favorably against Cas9 references, the commonly used enzyme for gene-editing tasks, with improved specificity. Additionally, we demonstrated multi-target editing with similar improved activities thanks to the RNA-processing activity of the Cas12a system. This compact, multi-target editing tool has the potential to assist in understanding multi-gene interactions, and it paves the way for a gene therapy method for human diseases that complements existing tools, particularly suitable for polygenic disorders and diseases requiring long-sequence corrections.